Reflecting the significance of family bonding in my artwork / Noor A’yunni Muhamad - Muhamad, Noor A’yunni (2013)
Family bonding is one of the important elements that should exist in family institution.It is because a lot of amazing things can happen when family meet, sit and do things together. When I’m doing my readings through internet and books, I can find that family bonding is actually related to human bonding. What I understand about human bonding is, it is a development of a relationship which usually can be referred to relationship between family and friends. However, the most important thing in family bonding is togetherness, intimacy and communication. Without those element, ‘family’ will be just a name. In my artwork, I tried to capture the significance of ‘family bonding’ due it is all about my own experience being a wife, mother, a student and a daughter. Since I have to do several works in one time, I tried so hard to keep the bonding between my family and myself ‘alive’ so that our family keep on getting stronger day by day. This research is significance to me and to public because my main intention is to preserve memories especially my happy moments with public so that the viewer can feel the same feelings as I feel in family bonding. To complete this research, I choose installation as my main approach. With installation, I will installed some of my family’s personal thing which is cloths and construct it as my body of artwork. By doing this kind of method, I can explore and express more about how do I feel in terms of ‘togetherness or even communication in family bonding’ concept.